Interlayer residual stress analysis of steel bridge deck pavement during gussasphalt pavement paving. (21st March 2022) - Liu, Yang; Qian, Zhendong; Gong, Minghui; Huang, Qibo; Ren, Haisheng
Highlights: A laboratory test was developed to evaluate the thermal resistance of waterproof bonding materials. The interfacial thermal resistance parameter was determined by the laboratory test and numerical simulation. Interlayer residual stress remain in the SBDP after the high-temperature pavement paving. The calculated maximum interlayer residual stress based on the CZM was 7.3 kPa. Abstract: The interlayer shear stress in the steel bridge deck pavement (SBDP) and interlayer shear performance of waterproof bonding material change significantly during the gussasphalt mixture (GAM) paving, and interlayer residual stress may remain in the SBDP after the paving, which can affect the long-term performance of SBDP. The interfacial thermal resistance (ITR) parameter was proposed to represent the thermal resistance performance of waterproof bonding material firstly. A laboratory test and numerical simulation were carried out simultaneously through simulating the temperature variations of OSBD and GAM pavement during the paving, and the ITR values for three common waterproof bonding materials were determined by the least square method. The direct shear test was used to measure the shear performance variations of waterproof bonding layer during the GAM paving. The cohesive zone model (CZM) in the finite element (FE) method was used to characterize the interlayer shear performance variations of waterproof bonding layer during the paving, and the interlayer residual stress in the SBDP was calculated by the numerical simulation. The results showed that the ITR of the methyl methacrylate (MMA) bonding material is about two times that of HYPER-PRIMER (HYP) epoxy resin, and the ITR of 2910-type epoxy asphalt bonding material approximates zero. The waterproof bonding material with higher ITR values can reduce the highest temperature of steel bridge deck and interlayer residual stress during the paving to some extent, and the maximum interlayer residual stress after the gussasphalt pavement paving reaches 7.3 kPa.